2018
DOI: 10.1111/jphp.13021
|View full text |Cite
|
Sign up to set email alerts
|

Self-emulsifying drug delivery systems and cationic surfactants: do they potentiate each other in cytotoxicity?

Abstract: Objectives The aim of this study was to evaluate the cytotoxicity of self‐emulsifying drug delivery systems (SEDDS) containing five different cationic surfactants. Methods Cationic surfactants were added in a concentration of 1% and 5% (m/m) to SEDDS comprising 30% Capmul MCM, 30% Captex 355, 30% Cremophor EL and 10% propylene glycol. The resulting formulations were characterized in terms of size, zeta potential, in‐vitro haemolytic activity and toxicity on Caco‐2 via MTT assay and lactate dehydrogenase releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 32 publications
(111 reference statements)
1
22
0
Order By: Relevance
“…The size distribution of complex loaded SEDDS FB was in the range of 40 ± 10 nm as described in Figure 3 B. Lam et al also observed an increase in the size of oily droplets by incorporation of cationic surfactants as the mean droplet size of SEDDS increased from 31 to 45 nm by incorporation of 1% 1-decyl-3-methylimidazolium chloride and to 55 nm by the incorporation of 5% octylamine. 26 During the incubation period neither precipitation nor phase separation of formulations was observed. The size distribution of the oily droplets of all formulations remained constant, the and PDI remained under 0.5 indicating monodisperse emulsions during the incubation time.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The size distribution of complex loaded SEDDS FB was in the range of 40 ± 10 nm as described in Figure 3 B. Lam et al also observed an increase in the size of oily droplets by incorporation of cationic surfactants as the mean droplet size of SEDDS increased from 31 to 45 nm by incorporation of 1% 1-decyl-3-methylimidazolium chloride and to 55 nm by the incorporation of 5% octylamine. 26 During the incubation period neither precipitation nor phase separation of formulations was observed. The size distribution of the oily droplets of all formulations remained constant, the and PDI remained under 0.5 indicating monodisperse emulsions during the incubation time.…”
Section: Resultsmentioning
confidence: 98%
“…The tertiary amine surfactant octylamine could not raise the zeta potential of SEDDS to a positive value even when added in a concentration of 5%, whereas the incorporation of 1% quaternary ammonium surfactants caused a dramatic shift in zeta potential to positive values. 26 To a certain extent CTL–polymer complexes seem to be located on the interface, as their incorporation in SEDDS had a significant impact on the zeta potential of the resulting oily droplets. Generally, SEDDS remained stable in the release medium despite size and zeta potential alterations caused by incorporating CTL–polymer complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility to optimize the formulation could be to change the cationic surfactant to one that has shown a lower cytotoxicity at the same concentration. Cationic surfactants such as alkyltrimethylammonium bromide, octylamine and 1-decyl-3-methylimidazolium have recently shown a lower cytotoxicity than benzalkonium chloride and its possible to design and prepare systems with nanometric size using these surfactants [36].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro hemolysis assay with exenatide-THA and exenatide-DOC as well as blank NCs was performed according to a previously reported protocol [27]. The dilution of 0.556 ml of human whole blood with 1.944 ml of sterile Dulbecco's PBS pH 7.4 was performed.…”
Section: In Vitro Hemolysis Assaymentioning
confidence: 99%
“…The in vitro hemolysis assay on human erythrocytes can be used as a rapid and reliable method to evaluate the effect of drug delivery systems on cell membranes [27,29]. In comparison to other cell types, the cell membrane of erythrocytes is very fragile.…”
Section: Cytocompatibilitymentioning
confidence: 99%